دور هيئة الأوراق والأسواق المالية السورية في حماية مصالح المستثمرين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Capital markets play a key role in economic growth. Also, it is well-known that the existence of capital markets and highly efficient stock exchanges provide many benefits to the economy and the financial system. The investment in securities and trading depends mainly on the disclosure of data and information on all the activities of the companies whose securities are traded in the market, in addition to the accuracy of these data and the speed of its publication in a fair, efficient and transparent manner, which greatly affects the interests of investors. So it was necessary to have a body that protects the interests of investors, and encourage them to invest in Damascus Stock Exchange because of its impact on the national economy as a whole. The purpose of this study is to know the extent to which the Syrian Securities and Exchange Commission is in the process of protecting the interests of investors; By designing a questionnaire and distributing it to a sample of persons, in addition to a field tour which included a few meeting of some employees in the Commission and the market as well. The study founded that the Commission has a great role in ensuring the accuracy of the information, simulating the reality of the company, and spreading the information quickly and fairly enough, without delay, and in the absence of any precedence for anyone to obtain this information, at almost no cost. despite the fact that speed is required, there is some delay in the decision when trading in the market. Correspondingly, the researcher noticed few in the number of investors, she attributed this result to the small number of companies whose shares are traded in the market and the lack of investment tools in addition to the lack of people’s culture in the financial markets and the existence of previous control of the market through the presence of a representative of the commission as a member of the board of directors of the market, which prevents the realization of large unrealistic losses or profits; thus, protecting the interests of investors and encouraging them to invest in Damascus Stock Exchange because of its impact on the national economy as a whole. تلعب أسواق رأس المال دوراً أساسياً في تحقيق النمو الاقتصادي، ومن المعروف أن وجود أسواق رأس المال وبورصات أوراق مالية ذات كفاءة عالية تمنح مزايا عديدة للاقتصاد والنظام المالي. ويعتمد الاستثمار في الأوراق المالية, وتداولها بالدرجة الأساس على الإفصاح عن البيانات والمعلومات عن جميع أنشطة الشركات التي يتم التعامل بأوراقها المالية في السوق, بالإضافة إلى دقة هذه البيانات وسرعة نشرها بما يحٌقق العدالة والكفاءة والشفافية, التي توثر كثيراً على مصالح المستثمرين. لذلك كان لابد من وجود هيئة تقوم بحماية مصالح المستثمرين, وتشجيعهم على الاستثمار في سوق دمشق للأوراق المالية لما له من أثر على الاقتصاد الوطني ككل. هدفت هذه الدراسة إلى معرفة مدى قيام هيئة الأوراق والأسواق المالية السورية بدورها في حماية مصالح المستثمرين. وذلك من خلال تصميم استبيان وتوزيعه على عينة من الأشخاص, بالإضافة إلى جولة ميدانية تخللها لقاء لبعض الموظفين في الهيئة والسوق. وقد توصلت الدراسة إلى أن للهيئة دور كبير في التأكد من دقة المعلومات, ومحاكاتها لواقع الشركة, وقيامها بنشر المعلومات بالسرعة الكافية, وبدون تأخير, وبعدالة أي لا يوجد أسبقية لأحد بالحصول على هذه المعلومات, وبتكاليف تكاد تكون معدومة, لكن هناك بعض التأخير في اتخاذ القرار عند التداول في السوق رغم أن السرعة هي المطلوبة, كما لاحظت الباحثة قلة عدد المستثمرين, وتعزو الباحثة هذه النتيجة إلى قلة عدد الشركات التي يتم التداول على أسهمها في السوق وقلة الأدوات الاستثمارية, بالإضافة لنقص ثقافة الناس بالأسواق المالية, ووجود رقابة سابقة على السوق وذلك من خلال وجود ممثل عن الهيئة كعضو في مجلس ادارة السوق, وذلك يحول دون تحقيق خسائر أو أرباح كبيرة غير حقيقية, وبالتالي تؤدي إلى حماية مصالح المستثمرين, وتشجيعهم على الاستثمار في سوق دمشق للأوراق المالية لما له من أثر على الاقتصاد الوطني ككل.